“Rogue” [DEspR+CD11b+] neutrophil subset correlates with severity in spontaneous intracerebral hemorrhage - Herrera, Victoria L. M.; Takahashi, Courtney E.; Nguyen, Mai Q.; Mosaddeghi, Julie Z.; Denis, Ridiane; Greer, David M.; Ruiz-Opazo, Nelson (Frontiers in Neurology, 2022)
Objective: Cumulative clinical, cellular and molecular evidence re-enforce the role of neutrophils in secondary brain injury in spontaneous intracerebral hemorrhage (sICH). However, since generalized neutrophil inhibition is detrimental, identification of targetable “rogue” neutrophil-subsets associated with sICH severity is key. Methods: In a pilot prospective observational study of consented sICH patients, we immunotyped whole blood to assess circulating neutrophil markers ( day-3 after ICH symptoms onset): a] DEspR±CD11b± neutrophils by flow cytometry, b] DEspR±CD11b± neutrophil extracellular trap (NET)-forming neutrophils by immunofluorescence-cytology, and c] neutrophil-lymphocyte ratio (NLR). Using Spearman rank correlation (r) with Bonferroni correction, we assessed association of neutrophil-markers with same-day clinical and neuroimaging parameters of sICH severity, index ICH-score and 90-day modified Rankin Scale (mRS) score, and potential interrelationships. As comparators, we assessed same-day plasma biomarkers elevated in sICH: interleukin-6/IL-6, myeloperoxidase/MPO, soluble-terminal complement complex/sC5b-9, endothelin-1/ET-1, and mitochondrial/nuclear DNA ratio (mt/nDNA ratio). Results: We detect strong correlations (r[n=13] >0.71, power >0.8, Bonferroni corrected pB < 0.05) for all three neutrophil markers with 90d-mRS score, differentially for DEspR+CD11b+ neutrophil-counts and NLR with perihematomal edema (PHE) volume, and for DespR+CD11b+ NET-forming neutrophil-counts with intraparenchymal hemorrhage (IPH)-volume. Only DespR+CD11b+ neutrophil-counts show strong correlation with index ICH score, same-day Glasgow Coma Scale (GCS) score, and with NLR and NET-forming neutrophil-counts. The sum of the ICH-score and three neutrophil markers exhibited the highest correlation: (r[n=13] 0.94, pB=10-5). In contrast, plasma biomarkers tested were elevated except for MPO, but exhibited no correlations in this pilot study. Conclusions: Strong correlation with multiple sICH severity measures, NET-formation and NLR identify DEspR+CD11b+ neutrophils as a putative “rogue” neutrophil subset in sICH. The even stronger correlation of the sum of three neutrophil markers and the index ICH-score with 90-day mRS outcome re-enforce early neutrophil-mediated secondary brain injury as a key determinant of outcome in sICH patients. Altogether, data provide basis for formal study of DEspR+CD11b+ neutrophil-subset as potential actionable biomarker for neutrophil-driven secondary brain injury in sICH. Data also show ex vivo analysis of sICH patient neutrophils as a translational milestone to refine hypotheses between pre-clinical and clinical studies.